(3ejRGf GdGYJOGd aj JQGLe GdQLGds - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s ((3eMeO Hf CMeO Hf YHOGddg Hf YHOGdQMef GdMfaj s)
(3ChdgG (B:s
(3GdMeO ddg dMce GdYOd GdYdi GdcHjQ s
(3BNQgG (B:s
(3hjfJgi HJQLeI GdSja GdBeOi GdeJcde, hgh BNQ JQGLe MQa GdSjf s
(3GfXQ Qbe (B536s
(3Qbe (B1275 (3JGQjNs
(3HBNQ GdfSNI hbajI eDQNI aj TgQ QHjY dChd SfI (B1127(3g`s
(3fSNI SGOSI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
Keywords: (3GdJGQjNs